ENTREPRENEURSHIP ISLAMI: INSPIRASI BISNIS SYARIAH BAGI MAHASISWA - Farhan Wicaksono; Nabiilah Annisa Fitri; Bunga Sasqia Nayla Salsa; Wida Nahyatul Nafisah; Abdul Fadhil (Cahaya Ilmu Bangsa Institute, 2024)
Islamic entrepreneurship is a business approach based on sharia principles, which is increasingly relevant among university students. This article discusses the inspiration and opportunities that students can take in developing business ethics, students can not only achieve financial success, but also contribute to the welfare of society. Through case studies and real-life examples, this article aims to provide insight and motivation for students to start and manage sustainable and socially responsible businesses. This article also uses literature research, qualitative research, and field observation methods.